1998
DOI: 10.1104/pp.116.2.845
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Plasma Membrane Ca2+-ATPase from Radish Seedlings by Calmodulin-Agarose Affinity Chromatography1

Abstract: The Ca 2؉ -ATPase of the plasma membrane (PM) of germinating radish (Raphanus sativus L.) seeds was purified by calmodulin (CaM)-affinity chromatography using a batch procedure. PM purified by aqueous two-phase partitioning was solubilized with n-dodecyl ␤-D-maltoside and applied to a CaM-agarose matrix. After various washings with decreasing Ca 2؉ concentrations, the Ca 2؉ -ATPase was eluted with 5 mM ethylenediaminetetraacetate (EDTA). The EDTA-eluted fraction contained about 25% of the loaded Ca 2؉ -ATPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 46 publications
4
40
0
2
Order By: Relevance
“…Calmodulin stimulated ATPase activity by approximately sixfold in a dose-dependent manner, showing a half-maximum activation at ‫01ف‬ nM for SCaM-1 (Figure 9) or bovine calmodulin (not shown). This value represents a higher K 1/2 than that reported for ACA2p (K 1/2 ϭ 30 nM bovine calmodulin), in agreement with prior findings on the biochemical properties of enzymes purified from plant tissues, that is, that Ca 2ϩ pumps from the plasma membrane have a stronger binding affinity for calmodulin than do pumps from the tonoplast (Askerlund, 1996(Askerlund, , 1997 or other endomembranes (Dainese et al, 1997;Bonza et al, 1998). The greater calmodulin binding affinity of SCA1p also might be attributable to the The presence of an N-terminal regulatory domain in SCA1p was demonstrated by an N-terminal deletion that resulted in a calmodulin-independent (i.e., deregulated) pump with kinetic properties similar to those of a full-length pump stimulated by calmodulin.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Calmodulin stimulated ATPase activity by approximately sixfold in a dose-dependent manner, showing a half-maximum activation at ‫01ف‬ nM for SCaM-1 (Figure 9) or bovine calmodulin (not shown). This value represents a higher K 1/2 than that reported for ACA2p (K 1/2 ϭ 30 nM bovine calmodulin), in agreement with prior findings on the biochemical properties of enzymes purified from plant tissues, that is, that Ca 2ϩ pumps from the plasma membrane have a stronger binding affinity for calmodulin than do pumps from the tonoplast (Askerlund, 1996(Askerlund, , 1997 or other endomembranes (Dainese et al, 1997;Bonza et al, 1998). The greater calmodulin binding affinity of SCA1p also might be attributable to the The presence of an N-terminal regulatory domain in SCA1p was demonstrated by an N-terminal deletion that resulted in a calmodulin-independent (i.e., deregulated) pump with kinetic properties similar to those of a full-length pump stimulated by calmodulin.…”
supporting
confidence: 78%
“…Biochemical evidence previously suggested the presence of a calmodulin-regulated Ca 2ϩ pump in the plant cell plasma membrane (Evans, 1994;Bonza et al, 1998), but the corresponding gene for this was not identified until now. In this study, both membrane fractionation and cytology indicated that SCA1p was located in the plasma membrane, and biochemical and genetic evidence demonstrated that SCA1p was a calmodulin-stimulated Ca 2ϩ pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PM Ca 2+ -ATPase has been studied extensively in both animal and plant cells using either biochemical or cytochemical methods [8][9][10], [13], [14], [18], [25], [26]. In biochemi-cal assay with cell free preparation, Mg 2+ ions must be added to the reaction medium in addition to the Ca 2+ for the activation of the Ca 2+ -ATPase [8], [9], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane (PM) Ca 2+ -ATPase plays a crucial role in controlling cytosolic Ca 2+ concentration [8][9][10][11][12][13][14]. The PM calcium-pumping, ATPase uses the energy supplied by the hydrolysis of ATP to transport calcium ions from the cytoplasm to the extracellular space.…”
Section: Introductionmentioning
confidence: 99%